KEPRIBADIAN PENDIDIK DALAM PERSPEKTIF HADIS - Fahmi Sahlan (Almarhalah | Jurnal Pendidikan Islam, 2021)
In line with the development and demands of human culture, parents cannot meet the needs of their children's educators. For that they submit their child's education to others. People who accept the mandate of parents to educate children are called teachers. The teaching profession is a noble profession because in addition to studying one's knowledge, it also demands that someone have noble morals.It seems that the most important factors in the teaching profession today are only scientific and academic qualifications. Meanwhile, other factors such as wisdom and wisdom which are moral attitudes and behaviors are no longer essential. As a result, the moral exemplary of the teachers is no longer so important in the educational process, what is more important is the skills and expertise in teaching science which is their duty.Therefore, everyone who will carry out teacher duties must have a personality that is in accordance with Islamic teachings and is even more required to have a teacher personality. Personality is the most important factor for a teacher.Â